Time and risk factors for death among smear-positive pulmonary tuberculosis patients in the Health District of commune VI of Bamako, Mali, 2016 - Yaya Ballayira; Pauline Kiswendsida Yanogo; Bakary Konaté; Fadima Diallo; Bernard Sawadogo; Simon Antara; Nicolas Méda (BMC, 2021)
Abstract Background The End Tuberculosis (TB) Strategy aims to achieve 90% reduction of deaths due to TB by 2030, compared with 2015. Mortality due to tuberculosis in Mali was 13 per 100,000 inhabitants in 2014 and 11 per 100,000 inhabitants in 2017. Risk factors for death are not known. The objective of this study was to determine the time and risk factors for death in pulmonary TB patients with positive microscopy. Methods We conducted a retrospective cohort study from October to December 2016 in Commune VI of Bamako. Smear positive cases pulmonary tuberculosis from 2011 to 2015 were included. We reviewed the treatment registers and collected sociodemographic, clinical, biological and therapeutic data. Median time to death and hazard ratio (HR) were estimated by the Kaplan-Meier method and a Cox regression model, respectively. Results In total, we analysed 1362 smear positive cases of pulmonary TB including 104 (8%) HIV positive and 90 (7%) deaths. The mean age was 36 ± 13 years, the sex ratio of males to females was 2:1. Among the deaths, 48 (53%) occurred during the first 2 months of treatment. Age ≥ 45 years (HR 2.09 95% CI [1.35-3.23]), weight <  40 kg (HR 2.20 95% CI [1.89-5.42]), HIV unknown status (HR 1.96, 95% CI [1.04-3.67]) and HIV-positive (HR 7.10 95% CI [3.53-14.26]) were significantly associated with death. Conclusions The median time to death was 2 months from the start of treatment. Independent risk factors for death were age ≥ 45 years, weight <  40 kg, unknown and positive HIV status. We recommend close monitoring of patients over 45 years, HIV testing in those with unknown status, an adequate care for positive HIV status, as well as a nutritional support for those with weight below 40 kg during the intensive phase of TB treatment.